A study of the Huntington's disease associated trinucleotide repeat in the Scottish population. Issue 12 (December 1993) - Barron, L H; Warner, J P; Porteous, M; Holloway, S; Simpson, S; Davidson, R; Brock, D J
Abstract : Accurate measurements of a specific CAG repeat sequence in the Huntington's disease (HD) gene in 337 HD patients and 229 normal controls from the Scottish population showed a range from 35 to 62 repeats in affected subjects and eight to 33 in normal subjects. A link between early onset of symptoms and very high repeat number was seen. For HD patients with the most common affected allele sizes (39 to 42 repeats) absolute repeat size was a poor index for the age at onset of symptoms. There was variability in the transmitted repeat size for both sexes in the HD size range. We observed a significant increase of repeat size for paternal transmission of the disease and greater instability for paternally transmitted CAG repeats in the HD size range.